A case study of disengaged adolescent girls' experiences with teaching games for understanding in physical education. Issue 3 (2nd September 2019) - Bracco, Elizabeth; Lodewyk, Ken; Morrison, Hayley
ABSTRACT: This case study served to investigate six adolescent girls', who were identified as disengaged in physical education (PE), feelings about their experiences in a Teaching Games for Understanding (TGfU) unit and how TGfU might support their engagement in PE. A two-week (6-lesson) TGfU territorial games unit was taught by a guest instructor. Data were collected from observational field notes, focus group interviews (pre-and post-unit), and individual interviews (post-unit). The whole child approach – understanding the physical, cognitive, and affective domains of learning and experience – was used to better understand the participants' experiences. Students experienced heightened participation and effort, learning, affect, and motivation in the TGfU-games unit. TGfU was beneficial due to its student and game-centred nature; however, students also had some reservations (time and sport choices). Ultimately, TGfU can support girls' engagement in PE, captivating them and encouraging them to elevate their participation in a holistic way.